Argonaute 2 targets viral transcripts but not genomes of RNA viruses during antiviral RNA interference in Drosophila. - Emanuele G Silva; Isaque J S de Faria; Álvaro G A Ferreira; Thiago Henrique L Jiran; Carlos F Estevez-Castro; Juliana N Armache; Siad C G Amadou; Yann Verdier; Joëlle Vinh; Karim Majzoub; Carine Meignin; Gabrielle Haas; et al. (PLoS Pathogens)
RNA interference (RNAi) mediated by the small interfering RNA (siRNA) pathway is a major antiviral mechanism in insects. This pathway is triggered when double-stranded RNA (dsRNA) produced during virus replication is recognized by Dicer-2, leading to the formation of virus-derived siRNA duplexes. These siRNAs are loaded onto the programmable nuclease Argonaute-2 (AGO2), with one strand serving as a guide to target and cleave fully complementary sequences of viral RNAs. While siRNAs are generated from viral dsRNA, the specific viral RNA species targeted for silencing during RNA virus replication remains unclear. In this study, we characterized the primary viral RNA targets of the Drosophila siRNA pathway during infections caused by negative and positive RNA viruses, namely Vesicular stomatitis virus (VSV) and Sindbis virus (SINV). Our findings reveal that polyadenylated transcripts of VSV and SINV are the major targets of silencing by the siRNA pathway during infection, likely when they are poised for translation. Consistent with earlier findings, we show that AGO2 is associated with ribosomes in control and virus infected cells. Therefore, we propose that the inhibition of the replication of RNA viruses in Drosophila results from the silencing of incoming viral transcripts, facilitated by the association of AGO2 with ribosomes.